Premature Rupture of Membranes in a Pregnant Patient with Systemic Lupus Erythematosus and Lupus Carditis: A Case Report - Wardani, Anisa Karamina; Nova Kurniati; Norman Djamaludin; Erwin Sukandi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease associated with significant maternal and fetal risks, especially during pregnancy. Lupus carditis and premature rupture of membranes (PROM) pose additional challenges in managing such pregnancies. Case presentation: A 21-year-old woman with a history of SLE and lupus carditis presented at 34 weeks gestation with premature rupture of membranes. Her medical history was notable for regular follow-up and treatment for SLE manifestations, including mucocutaneous involvement and microcytic hypochromic anemia. Physical examination revealed characteristic signs of SLE, and echocardiography confirmed dilated cardiomyopathy. Following a multidisciplinary approach, a cesarean section was performed, resulting in the successful delivery of a healthy neonate. Conclusion: This case highlights the importance of a coordinated multidisciplinary approach in managing complex pregnancies involving SLE, lupus carditis, and PROM. Early diagnosis, close monitoring, and timely intervention are crucial for optimizing maternal and fetal outcomes in such cases.